Analysis on match factor change according to introducing VAR system in K League - Cho, J.-E.; Shin, J.-H. (Korean Journal of Sport Science, 2021)
Purpose: The purpose of this study is to analyze the changes in the game factors since the introduction of the VAR system and discuss the meaning of the changes in the K-League. Methods: The game factors related to referee decisions (goal, penalty kick, offside, foul, yellow card, red card, additional time) were divided into home and away team and analyzed by two-way ANOVA for 556 games before and 583 games after the VAR system was implemented. All game factors that occurred during the match and additional time were analyzed as independent t-test before and after the implementation of the VAR system. Results: First, there was no statistically significant difference between a goal and a penalty kick. Second, the offside was significantly reduced throughout the home team, away team and the entire game(p<.001). Third, fouls were significantly reduced in home teams, away teams and the entire game (p<.01). Fourth, yellow cards were significantly reduced in both home and away teams and the entire game(p<.001). The red card increased significantly throughout the home team, away team, and the entire game(p<.001). Sixth, the additional time showed no difference the first half and the entire game, and was a little reduced in the second half (p<.05). Conclusions: As a result of this study, players should not anticipate offside decision and stop playing in critical situations that may lead to a score or penalty kick, and continue playing until the referee makes a final decision. In addition, all red card situations are review through the VAR system, so excessive foul play or unnecessary behavior should be avoided. K-League referees are required to make a more accurate decision in the red card situation, and the time wasted by the VAR system during the game is not much.